Type A4 truncus arteriosus: series of 3 cases focused on dual source multidetector CT angiogram findings - Verma, Amit Kumar; Rawat, Anil; Mishra, Siddharth; Dikshit, Nitin Arun (International Journal of Research in Medical Sciences, 2021)
Truncus arteriosus (TA) is a rare congenital cardiac anomaly caused by failure of normal conotruncal septation during the fetal development. This aberration leads to a common ventricular outflow artery over the malaligned large ventricular septal defect (VSD), supplying systemic, coronary and pulmonary circulation. People with such anomalous anatomy show variable presentation from early childhood to adult life depending on the severity of defects. We here present three cases of truncus arteriosus with aortic interruption / hypoplasia-coarctation (type A4 truncus arteriosus) with focus on relevant dual source MDCTA findings.